Portfolio pumping no mercado acionário brasileiro - Orefice, Marcelo de Castro (2017)
In this dissertation, we discuss the practice of portfolio pumping in Brazil. Although the topic is recurrent in other countries, few studies provide this analysis for the Brazilian case. The statistical study is elaborated in three stages: first, we considered Brazilian investment funds‟ shares for the period from September 2011 to June 2016, estimating daily abnormal returns of those funds based on the Ibovespa, considering and not considering the adjusted beta of the portfolios of those funds. Our results suggest that the practice of portfolio pumping is more frequent at the end of months ex-semester than at the end of semesters. When we consider the beta adjusted to calculate abnormal returns of the funds, we found a greater significance for the existence of this practice. In the second step, the funds were ordered based on their performance in the previous period (by month, semester, and year), which resulted in few relevant results for the analysis of the topic, despite what is proposed by the principal-agent problem literature. In the last step, we analyzed the practice of portfolio pumping in stocks traded on BM&F Bovespa, ordering them by their participation in the portfolios and by their Market Cap. The results indicated that the stocks with greater presence in the portfolios of the investment funds have higher abnormal returns at the end of the periods, reinforcing the thesis that this increase in stock prices in those moments may be a consequence of a deliberate action taken by the managers of those funds